Evaluation of the growth of solutions of systems of linear differential equations of the $n$th order - Mokhon’ko, A.; Mokhon’ko, O. (Ukrains’kyi Matematychnyi Zhurnal, 2025)
UDC 517.925.7For a system of linear differential equations of the $m$th order with coefficients holomorphic in a neighborhood of $∞,$ we obtain an a priori estimate of growth for the $n$-valued ($n \in \mathbb{N}$) analytic vector solutions of the system via the estimate for the order of growth of its coefficients.